Malaysian PBL Approaches: Shaping World-Class TVET Skills towards IR 4.0 - Rohanai, Reyanhealme; Othman, Hasyamuddin; Mat Daud, Khairul Azhar; Omar, Nurul Huda; Ahmad, Maimunah; Ismail, Mohd Erfy; Sulaiman, Abdullah (2020)
An Industrial Revolution 4.0 promoted by Malaysian government entitles the rapid growth of manufacturing sector thus promotes a multi-level of workforce and skilled work force needed to satisfy the rapid technological development application. The challenges arise on preparing the individuals to meet with the current business at adequate skills level and the student need to be prepared in such way satisfied the business expectations. Looking into this situation, this paper aims to study the concept of correlation between active learning method known as Problem-Based Learning (PBL) Method and required employability skills in TVET. As an initiative to enrich the future opportunity on empowering TVET skills, this study assumes that there is positive relationship between employability skills and PBL approaches in improving student’s quality and skills. The method of study involves documentation analysis on previous research to proves the importance of employability skills in enhancing student’s competencies and the effectiveness of Problem-Based Learning Method in preparing the students to meet the expectations. The main findings of this study claimed that there was a positive relationship between employability skills and PBL learning method. Result acknowledge that PBL has the ingredients to help develop employability skills and student’s behavior. Through PBL, students learn to become more associates in the teaching and learning processes as they take responsibility throughout the learning process. It would suggest that the educational institution should emphasize the needs of the industry and students by creating awareness and guiding the students in self-analysis and in acquisition of skills.